Commercial technologies of CRIJAF for cost-effective fibre production - Sinha, M K; Ramasubramanian, T; Naik, R K; Mahapatra, B S (Indian Farming, 2015)
CRIJAF has organized several extension programmes such as front line demonstrations, meetings and national level trainings in collaboration with line departments to assess and transfer the production technologies to the farmer’s fields, as most of the farmers are unaware about the advanced technologies developed at CRIJAF. It has been proved that the technologies developed at CRIJAF such as improved varieties, line sowing by manual seed drill, mechano-microbial retting could reduce the cost of cultivation and significantly enhanced the net return as compared to the farmers’ practice. CRIJAF is leading the way to mechanized agriculture by developing commercial and viable technologies and thus, transforming the lives of the resource-poor farmers.